Applicability of Recent Dyslipidemia Guidelines in Clinical Practice - Erwinanto Erwinanto (ACI (Acta Cardiologia Indonesiana), 2019)
Atherosclerotic plaque rupture is closely related to acute coronary syndromes.Stabilization of atherosclerotic plaque which slashes plaque rupture is as importantas regression ofplaque size for reducing cardiovascular events. Dyslipidemia therapy targeting to decrease LDL cholesterol reduces cardiovascular events such as acute myocard infarct, stroke, and death which are suggested to be the result of plaque stabilization. Dyslipidemia therapy also regress atherosclerotic plaque into a smaller volume. Plaque regression improves coronary flow responsible for the reduction of myocardial infarction incidence in patients with coronary heart disease (CHD).This paper consists of two parts. The first part discusses the evidence of cardiovascular event reduction with statin. The second part describes dyslipidemia management based on the 2017 Indonesian Heart Association (PERKI) Guideline on the Management of Dyslipidemia